Solar blind photodetector based on epitaxial zinc doped Ga2O3 thin film. Issue 5 (5th January 2017) - Alema, Fikadu; Hertog, Brian; Ledyaev, Oleg; Volovik, Dmitry; Thoma, Grant; Miller, Ross; Osinsky, Andrei; Mukhopadhyay, Partha; Bakhshi, Sara; Ali, Haider; Schoenfeld, Winston V.
Abstract : We report on the fabrication and characterization of solar blind photodetectors (SBPs) based on undoped β‐Ga2 O3 and Zn doped (∼5 × 10 20 cm −3 ) β‐Ga2 O3 (ZnGaO) epitaxial films with cutoff wavelength of ∼260 nm. The epilayers were grown on c‐sapphire by the metal organic chemical vapor deposition technique and their structural, electrical and optical properties were characterized using various methods. As grown films have a large number of defects, resulting in detectors with enhanced internal gain, hence, high spectral responsivity >10 3 A/W. Post growth annealing in oxygen improved the quality of the epilayers, leading to detectors with reduced dark current (∼nA to ∼pA) and increased out of band rejection ratio. At 20 V bias, a ZnGaO detector showed a peak responsivity of 210 A/W (at 232 nm) and an out of band rejection ratio (i.e., R232 nm/R320 nm) of 5 × 10 4 . Alternatively, for a β‐Ga2 O3 detector these parameters were found to be five times and three times lower, respectively, suggesting that ZnGaO detectors have superior performance characteristics. These results provide a roadmap toward achieving high responsivity SBPs based on epitaxial ZnGaO films, laying a solid foundation for future applications.